Myanmar Early Grade Reading Assessment for the Yangon Region : 2014 Results Report - World Bank (World Bank, Bangkok, 2017)
This report presents the work to adapt the EGRA to the Myanmar language and to administer it (and its questionnaires) in the Yangon region. The results of this exercise were analyzed to assess how valid and reliable this adapted tool is for the Myanmar language. Other aims of the analysis were to define core learning standards in early primary grades, and identify potential explanatory factors for differences in EGRA scores among schools. The specific information from EGRA can help guide the Ministry of Education in prioritizing future interventions that best help students improve their reading skills in early grades, as well as support the development of measurable, comparable benchmarks for students’ progress. The report is organized into six sections, including the introduction. Section two briefly reviews the reforms and goals of the education sector in Myanmar and the major challenges that helped define the research questions for the EGRA. Section three describes the most relevant education theories about learning to read in the early grades and the way these are reflected in the design of the EGRA. Section four outlines the design and implementation of the study and tools, and how they took into account the information needs of education stakeholders and the specificities of the language and education sector in Myanmar. Section five presents the methodology and results of the study for non-experts, with the methodology and statistical analyses detailed in annex five. Section six concludes with a summary of recommendations.